2021
DOI: 10.1097/jom.0000000000002279
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Outcomes Among British Healthcare Workers—Lessons From the First Wave of the Covid-19 Pandemic

Abstract: Objective: To ascertain the level of psychological distress, using validated psychology tools, among British National healthcare workers (HCW) during the first wave of the Covid-19 crisis. Methods: A multi-centre, anonymized, all-comer staff survey across 3 hospitals in Lancashire, England during the Covid-19 first wave (April to June 2020), consisting of Patient Health Questionnaire (PHQ-9), Perceived Stress Scale-10 (PSS-10), Generalized Anxiety Disorder-7 (GAD-7), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
2
10
1
Order By: Relevance
“…The first and second waves of the COVID pandemic carried so much panic, stress, and anxiety for healthcare providers. 24 , 25 …”
Section: Discussionmentioning
confidence: 99%
“…The first and second waves of the COVID pandemic carried so much panic, stress, and anxiety for healthcare providers. 24 , 25 …”
Section: Discussionmentioning
confidence: 99%
“…Regionally, HCPs working in North West England experienced high levels of psychological distress during the first wave of the COVID-19 pandemic (Debski et al, 2021). They added that HCPs living alone, having disabled dependents or a history of depression/ anxiety, were at increased risk of stress and anxiety and that resources should be targeted to "at risk" staff groups.…”
Section: Discussionmentioning
confidence: 99%
“…Burnout, exhaustion and disengagement have been found amongst academic radiographers across Europe due to increased workloads, creating a desire to leave the profession (Knapp et al, 2022). Regionally, HCPs working in North West England experienced high levels of psychological distress during the first wave of the COVID‐19 pandemic (Debski et al, 2021). They added that HCPs living alone, having disabled dependents or a history of depression/ anxiety, were at increased risk of stress and anxiety and that resources should be targeted to “at risk” staff groups.…”
Section: Discussionmentioning
confidence: 99%
“…10 Numerous studies have reported on the negative impacts of the COVID-19 pandemic on mental health and well-being in healthcare workers, with a high or increased prevalence of depression, anxiety, insomnia, stress, posttraumatic stress disorder symptoms, and burnout. [11][12][13][14][15][16][17][18][19][20][21][22][23][24] A recent meta-analysis study reviewed 83 studies on mental health in healthcare workers during the COVID-19 pandemic and reported a pooled prevalence of 41.4% for anxiety, 37.1% for depression, 44.9% for stress, and 43.8% for insomnia. 23 Moreover, several studies reported high or increased prevalence of adverse skin reactions from the prolonged use of PPE.…”
Section: Introductionmentioning
confidence: 99%
“…However, there has been a paucity of research on how the COVID-19 pandemic affected the risk of occupational injury, whereas considerable research has addressed its negative effects on mental health in healthcare workers. [11][12][13][14][15][16][17][18][19][20][21][22][23][24] A Turkish study reviewed hospital medical records of patients with occupational accidents between 2019 and 2021, and reported that occupational accidents increased in the healthcare and transportation sectors during the pandemic, while all other sectors showed decreases. 31 To address the data gap, we conducted this study to assess the impact of the COVID-19 pandemic on occupational injury or illness incidence in nursing care facility workers.…”
Section: Introductionmentioning
confidence: 99%